Semi-empirical model for shear strength of RC interior beam-column joints subjected to cyclic loads. (1st December 2020) - Pauletta, Margherita; Di Marco, Caterina; Frappa, Giada; Somma, Giuliana; Pitacco, Igino; Miani, Marco; Das, Sreekanta; Russo, Gaetano
Highlights: A model for prediction of interior RC beam-column joint shear strength is proposed. The contributions of three concrete struts and steel reinforcements are considered. Bond forces transferred by reinforcing bars affect concrete struts contributions. Concrete struts provide a predominant contribution to joint shear strength. Vertical bars are more effective in providing shear strength than horizontal stirrups. Abstract: This paper proposes an extension to RC interior beam-column joints of a model for the shear strength prediction of exterior joints under seismic actions, already presented in the literature and based, for certain assumptions, on a previous work of Park and Mosalam. The necessary changes, due to the joints' different physical configurations, only one beam converging in exterior joints and two beams converging in interior ones, are introduced. In the proposed model, on the basis of mechanical considerations, a direct formula for interior joint shear strength accounting for the resisting contributions of three inclined concrete struts and of joint reinforcements, the column horizontal stirrups and intermediate vertical bars, is derived. In comparison to the model for exterior joints, three struts are considered instead of two and the influenced of the upper column axial load on the inclination of the concrete struts is taken into account. The coefficients of the contributions of the struts and reinforcements are calibrated using 69 test data sets available in the literature, selecting only cyclic tests showing joint shear failure. For the validation of the proposed model, the shear strength predictions obtained using the proposed expression are compared with those obtained from Kassem's model, Wang et al.'s formula and Kim and LaFave's formula, on a set of 28 specimens. It is also proposed a design formula, whose predictions are compared to those of Eurocode 8 and ACI Code.